Significance of forest fragments for conservation of endangered vascular plant species in southern Brazil hotspots. Issue 3 (3rd July 2019) - Tomadon, Leonardo da Silva; Dettke, Greta Aline; Caxambu, Marcelo Galeazzi; Ferreira, Igor José Malfetoni; Couto, Edivando Vitor do
ABSTRACT: The Brazilian Atlantic Forest and Brazilian Savanna (i.e., Cerrado) are classified as World Biodiversity Hotspots. Our goal was to analyze the spatial distribution of endangered species in both habitats within the Mourão River basin, southern Brazil. Forest remnants were mapped using Landsat 8 satellite images applying NDVI medium and landscape metrics. Locations of endangered species were added as an additional layer. The result was a map of 4015 forest remnants of which 97.66% were smaller than 50 ha, and 2.34% were larger than 50 ha. A total of 41 species was recorded in the Atlantic Forest fragments of the basin (total area: 25 502.6 ha), and 32 species in the Brazilian Savanna (total area: 8.6 ha). The forest fragment with the greatest richness of endangered species was Lago Azul State Park with 29 species endangered at the state level and six at the national level. The second and third most species-rich fragments corresponded to Brazilian Savanna fragments: Cerrado Ecological Station and Lote 7H. The integration of GIS, landscape metrics and spatial distribution of endangered species is an important tool for the identification of priority areas for biodiversity conservation.